COVID-19 health and social care access for autistic people: European policy review. Issue 6 (17th May 2021) - Oakley, Bethany; Tillmann, Julian; Ruigrok, Amber; Baranger, Aurélie; Takow, Christian; Charman, Tony; Jones, Emily; Cusack, James; Doherty, Mary; Violland, Pierre; Wroczyńska, Agnieszka; Simonoff, Emily; et al.
Abstract : Background: The global COVID-19 pandemic has had an unprecedented impact on European health and social care systems, with demands on testing, hospital and intensive care capacity exceeding available resources in many regions. This has led to concerns that some vulnerable groups, including autistic people, may be excluded from services. Methods: We reviewed policies from 15 European member states, published in March–July 2020, pertaining to (1) access to COVID-19 tests; (2) provisions for treatment, hospitalisation and intensive care units (ICUs); and (3) changes to standard health and social care. In parallel, we analysed survey data on the lived experiences of 1301 autistic people and caregivers. Results: Autistic people experienced significant barriers when accessing COVID-19 services. First, despite being at elevated risk of severe illness due to co-occurring health conditions, there was a lack of accessibility of COVID-19 testing. Second, many COVID-19 outpatient and inpatient treatment services were reported to be inaccessible, predominantly resulting from individual differences in communication needs. Third, ICU triage protocols in many European countries (directly or indirectly) resulted in discriminatory exclusion from lifesaving treatments. Finally, interruptions to standard health and social care left over 70% of autistic people without everyday support. Conclusions: The COVID-19 pandemic has further exacerbated existing healthcare inequalities for autistic people, probably contributing to disproportionate increases in morbidity and mortality, mental health and behavioural difficulties, and reduced quality of life. An urgent need exists for policies and guidelines on accessibility of COVID-19 services to be updated to prevent the widespread exclusion of autistic people from services, which represents a violation of international human rights law.